Digitalization and Passive SMEs Internationalization: A Case in Sanan Tempe Industry Cluster, Indonesia - Mega Noerman Ningtyas; Sudarmiatin Sudarmiatin; Heri Pratikto (Business and Investment Review, 2026)
Research Aims: The aim of this study is to examine how digitalization enables the internationalization process of micro enterprise in the Sanan Tempe Industry Cluster, Malang, Indonesia We focus n enterprises that did not originally intend to internastional markets. Design/Methodology/Approach: We conducted a qualitative single case study design, following Yin (2018). The case is Mekar Jaya Tempe was selected through purposive sampling as the most prominent and representative producer in the cluster. Data were collected through in depth semi structured interview, direct observation of the production site and digital presence and also documentary analysis of publicly accessible social media content. Data analyzed using thematic analysis following Braun & Clarker (2006), with themes reviewed against the Uppsala Model of Internationalization. Research Findings: Three inteconnectednes themes emerged from the data but these findings challenge the Uppsala Model asumption that internationalization is driven by sequential, conscious market commitment and reveal a theoritical distinct pathway in which digital tools enable cross border market entry without export intent. Conclusion: The concept of digitally mediated passive internationalization to describe the unintentional cross border movement of goods arising from domestic digital marketing activities.